Differential accumulation of callose, arabinoxylan and cellulose in nonpenetrated versus penetrated papillae on leaves of barley infected with Blumeria graminis f. sp. hordei. Issue 3 (20th August 2014) - Chowdhury, Jamil; Henderson, Marilyn; Schweizer, Patrick; Burton, Rachel A.; Fincher, Geoffrey B.; Little, Alan
Summary: In plants, cell walls are one of the first lines of defence for protecting cells from successful invasion by fungal pathogens and are a major factor in basal host resistance. For the plant cell to block penetration attempts, it must adapt its cell wall to withstand the physical and chemical forces applied by the fungus. Papillae that have been effective in preventing penetration by pathogens are traditionally believed to contain callose as the main polysaccharide component. Here, we have re‐examined the composition of papillae of barley ( Hordeum vulgare ) attacked by the powdery mildew fungus Blumeria graminis f. sp. hordei ( Bgh ) using a range of antibodies and carbohydrate‐binding modules that are targeted to cell wall polysaccharides. The data show that barley papillae induced during infection with Bgh contain, in addition to callose, significant concentrations of cellulose and arabinoxylan. Higher concentrations of callose, arabinoxylan and cellulose are found in effective papillae, compared with ineffective papillae. The papillae have a layered structure, with the inner core consisting of callose and arabinoxylan and the outer layer containing arabinoxylan and cellulose. The association of arabinoxylan and cellulose with penetration resistance suggests new targets for the improvement of papilla composition and enhanced disease resistance. Abstract : See also the Commentary by Hückelhoven